2016
DOI: 10.1155/2016/5205631
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion and Function Are Distinctly Altered by Sevoflurane Anesthesia in Diet-Induced Prediabetic Rats

Abstract: Preservation of myocardial perfusion during surgery is particularly important in patients with increased risk for perioperative complications, such as diabetes. Volatile anesthetics, like sevoflurane, have cardiodepressive effects and may aggravate cardiovascular complications. We investigated the effect of sevoflurane on myocardial perfusion and function in prediabetic rats. Rats were fed a western diet (WD; n = 18) or control diet (CD; n = 18) for 8 weeks and underwent (contrast) echocardiography to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…Some report decreased [ 8 , 13 , 17 , 18 ] others unchanged [ 19 ] or even improved [ 20 ] systolic function. Studies on cardiac function in obesity in the perioperative setting are rare, but have shown additional cardiodepressive effects of sevoflurane in diet-induced obese rats [ 8 ]. In our mild phenotype we found impaired fractional shortening but also load-independent end-systolic elastance, indicating that this is a true contractility effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some report decreased [ 8 , 13 , 17 , 18 ] others unchanged [ 19 ] or even improved [ 20 ] systolic function. Studies on cardiac function in obesity in the perioperative setting are rare, but have shown additional cardiodepressive effects of sevoflurane in diet-induced obese rats [ 8 ]. In our mild phenotype we found impaired fractional shortening but also load-independent end-systolic elastance, indicating that this is a true contractility effect.…”
Section: Discussionmentioning
confidence: 99%
“…(Contrast-enhanced) echocardiography was performed using a Siemens (ACUSON, Sequoia 512) device equipped with a 14 MHz linear array transducer as described previously [ 8 , 13 ]. Before infusion of contrast agent, contractile function was determined by visualizing the LV in short axis midpapillary view, and left ventricular end-systolic (ESD) and end-diastolic (EDD) diameters were determined in M-mode.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This negative effect can be explained by reduced activation of the ROS-mediated AMPK signaling pathway[ 123 ]. In another study, van den Brom et al[ 124 ] showed that sevoflurane has a stronger depressant effect on myocardial function than other agents, thus possibly increasing cardiac vulnerability to limited oxygen supply and increasing risk of ischemia during surgery.…”
Section: Immunomodulatory Effects Of Anesthetics In Obesitymentioning
confidence: 99%